2017
DOI: 10.1515/revneuro-2017-0036
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic underpinnings in Alzheimer’s disease – a review

Abstract: Abstract In this review, we discuss the genetic etiologies of Alzheimer’s disease (AD). Furthermore, we review genetic links to protein signaling pathways as novel pharmacological targets to treat AD. Moreover, we also discuss the clumps of AD-m ediated genes according to their single nucleotide polymorphism mutations. Rigorous data mining approaches justified the significant role of genes in AD prevalence. Pedigree analysis and twin studies suggest that genetic components are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 149 publications
0
11
0
1
Order By: Relevance
“…In contrast, most AD patients have late-onset symptoms of dementia with undefined causes. Recent results from genome wide association studies (GWAS) provide several genes that associated with AD (Lambert et al, 2013; Moustafa et al, 2018; Van Cauwenberghe et al, 2016); however, the mechanisms between these genes and AD pathophysiology remain to be elucidated.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…In contrast, most AD patients have late-onset symptoms of dementia with undefined causes. Recent results from genome wide association studies (GWAS) provide several genes that associated with AD (Lambert et al, 2013; Moustafa et al, 2018; Van Cauwenberghe et al, 2016); however, the mechanisms between these genes and AD pathophysiology remain to be elucidated.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…The three main causative genes ( APP, PSEN1 , and PSEN2 ) and one common genetic risk factor ( APOEε4 allele) have been identified. Large-scale GWAS studies found multiple additional risk loci for late-onset AD, with the associated genes mapping to the three principal pathways: cholesterol and lipid metabolism; immune system and inflammatory response; and endosomal vesicle cycling [ 132 ].…”
Section: Neat1/paraspeckles Are Dysregulated In Neurodegenerative Dismentioning
confidence: 99%
“…In previous work a lot of genes belonging to C 1 and C 2 communities had already been highlighted as linked to AD. For example RIN3 was found to play key roles in the development of AD ad in particular it resulted associated with AD risk [58, 59]. J.W.…”
Section: Resultsmentioning
confidence: 99%